A novel proposed flexible thin-film solar annular thermoelectric generator. (25th January 2021) - Cao, Yan; Abu-Hamdeh, Nidal H.; Moria, Hazim; Asaadi, Soheil; Alsulami, Radi; Sadighi Dizaji, Hamed
Graphical abstract: Highlights: Thin-film annular solar thermoelectric is proposed. The effect of geometric parameters are investigated. Most parameters shows a peak point (optimum condition). The generator is applicable in micro-scale electronic devices. Abstract: Contrary to the non-flexible thermoelectric generator, flexible thermoelectric can be employed for curved and variable surfaces through a wide range of applications such as biomedical, wearable medical devices, self-charged electronic devices and so on. Hence, this paper proposes a thin-film flexible annular solar thermoelectric generator in a specific unique structure which can be used in mentioned applications. In order to identify the behaviour of the proposed thin-film generator, a comprehensive simulation is carried out via a validated 3D numerical simulation to identify the impact of all fluid-flow and geometrical parameter. It is noted that, as the scale of the systems is so small and thin, the change of any parameter of any part of the generator significantly changes the performance of the thermoelectric. Hence, the impacts of all thermal and geometric parameters on output characteristics of the generator are investigated in this paper and the optimum ranges are clarified. The results showed that the increment of the number of the legs increases and then decreases the intensity of the output power. Hence, an optimum leg number (which is around 20) should be considered. A peak point was also observed for effect of thermoelectric inner radius as well with optimum value of 3.6 mm. The impact of leg thickness was found more effective than the impact of leg length on output power. Thicker leg provides higher output power while the longer leg does not show significant impact. The substrate should be thin as much as possible with high thermal conductivity to achieve the maximum output power. Other remarkable results are presented in this paper.